Networks of bishops, networks of texts Manuscripts, legal cultures, tools of government in Carolingian Italy at the time of Lothar I - De Angelis, Gianmarco; Veronese, Francesco (Reti Medievali E-Book, 2022)
This volume is the first one in a collection connected to the PRIN project on Ruling in hard times. Patterns of Power and practices of government in the making of Carolingian Italy. Its focus lays on bishops and their networks of relationships in late-8th and 9th-century Italy. The episcopal contribution to the inclusion of the Lombard kingdom in the Carolingian social and political landscape is especially analyzed from the perspective of the cultural exchanges (of ideas, texts, and manuscripts) that bishops created or used to carry out their public and pastoral duties. Each paper focuses on a specific episcopal figure or area, reconstructing the scope and extent of the relationships of which they were the pivot. The aim is to provide as comprehensive a picture as possible of the cultural networks that crossed Carolingian Italy and the ways in which bishops shaped and made use of them.